KONTRIBUSI TEKNOLOGI PENGENDALIAN HAMA TERPADU PADA PENURUNAN PENGGUNAAN PESTISIDA: KASUS PRODUKSI PADI DI YOGYAKARTA - Joko Mariyono (Jurnal Matematika Sains dan Teknologi, 2006)
The objective of this study is to examine the contribution of integtated pest management technology to significant decrease in use of pesticides in rice production. This study was conducted in Yogyakarta, where the technology has been intensively disseminated through farmer’s field school. Aggregate data shows that the use of pesticides declines significantly after the introduction of the technology. A constant elasticity of input demand model was employed in this study. The results of the study show that IPM technologi was increasingly disseminated during 1989-1998. At the same period, pesticide use declined significantly. The decrease in pesticide use was affected by the increase dissemination of IPM technology and the increase in relative price of pesticides.